Folkloristični portreti iz 20. stoletja Do konstituiranja slovenske slovstvene folkloristike - Stanonik, Marija (ZRC SAZU, Založba ZRC, 2013)
The monograph ('Folkloristic Portraits from 20th Century. Till the constitution Slovenian folkloristics') is chronical and logical continuation of the first book Folk portraits of three centuries. The author deals with 14 personalities who were active in the first half of the 20th century, ie. till the constitution of Slovenian folkloristics: J. Polivka, M. Murko, I. Koštial, I. Grafenauer, F. Kotnik, J. Kelemina, J. Glonar, F. Stele, J. Glazer, P. Zablatnik, V. Möderndorfer, L. Zupanc, J. Dolenc, M. Matičetov.